The Concept of Hadhanah (Child Custody) After Divorce in Islamic Civil Law: - Arief Hanif, Hamdan; Nissa Salsabila, Aulia; Hubur, AA (STAI Publisistik Thawalib Jakarta, 2023)
Divorce increases every year, and hadhanah is essential to maintain balanced child custody in accordance with Islamic law and the principle of prioritizing benefit (maslahah). The purpose of this study is to explain and describe hadhanah in depth. The research uses qualitative methods with a literature study approach, employing documentation for data collection, data reduction, and presentation for processing, and ensuring validity through source triangulation. This study reveals that the implementation of hadhanah (child custody) in Indonesia has moved beyond purely normative considerations, such as gender or lineage, and now prioritizes the principle of the best interests of the child. Judges increasingly take into account the child’s psychological well-being, the emotional and financial capacity of the guardian, and the stability of the post-divorce environment. The research highlights the need to reinterpret classical fiqh in light of contemporary social contexts. Thus, the findings promote a more adaptive approach to Islamic law one that ensures holistic protection for children in hadhanah cases. Conclusion: This study provides positive insight for parents in educating their children after divorce.